Immunohistochemical Evaluation of the Hedgehog Route as a Potential Prognostic Factor in Hepatocellular Carcinoma - João Paulo Imperes Lira; Jesus Junior Faria Rosa; Ronniel Morais Albuquerque; Thiago Almeida Pereira; Paula Vieira Teixeira Vidigal (Sociedade Brasileira de Patologia Clínica, 2022)
ABSTRACT Introduction Hepatocellular carcinoma (HCC) is the most common primary malignant neoplasm in the liver. HCC develops gradually from multiple stages that control proliferation and apoptosis. In hepatocarcinogenesis, multiple signaling pathways were already described, such as the Hedgehog pathway (Hh). However, few studies have investigated the expression of Hh proteins as a potential prognostic factor in human HCC. This study aimed to investigate the expression of the Shh protein in HCC and to correlate with clinical and morphological prognostic characteristics of the tumor. Methods Immunohistochemical expression of Shh protein in tumor and cirrhotic parenchyma was performed in 36 HCC samples from patients who underwent liver transplantation at Clinical Hospital - UFMG. Correlation between the Shh tumor expression and etiology, number of nodules, size of the nodules, levels of alpha-fetus-protein (AFP), MELD score, tumor differentiation, and vascular invasion were performed. Results In our study, Shh protein labeling gradually increased from the normal to the cirrhotic and neoplastic parenchyma. Degree of tumor differentiation and vascular invasion were correlated with high Shh protein expression (p = 0.014 and p = 0.003, respectively). The other variables did not show a statistically significant correlation with Shh labeling. Conclusion Hedgehog pathway has importance in hepatocarcinogenesis. The immunohistochemical study of the Hh signaling pathway may have a promising role as a prognostic factor for HCC, especially due to the positive correlation between the Shh expression and the degree of tumor differentiation and invasion vascular.